Tethering the Extensor Apparatus Limits PIP Flexion Following K-wire Placement for Pinning Extra-articular Fractures at the Base of the Proximal Phalanx. (December 2016) - Sela, Yaron; Peterson, Caitlin; Baratz, Mark E.
Background: Closed reduction with percutaneous Kirschner wires (K-wires) is the most minimally invasive surgical option for stabilizing phalanx fractures. This study examines the effect of K-wire placement on proximal interphalangeal (PIP) joint motion.Methods: PIP joint flexion was measured in the digits of 4 fresh-frozen cadaver hands after placing a suture loop through the flexor tendons and placing tension on the flexors via a mechanical scale. The load necessary to flex the PIP joint to 90° or to maximum flexion was recorded. The load was removed and K-wires were inserted in 3 locations about the metacarpophalangeal joint (MPJ): through the extensor tendon and across the MPJ, adjacent to the extensor tendon insertion site and across the MPJ, and through the sagittal band and into the base of the proximal phalanx (P1). The load on the tendons was reapplied, and angles of PIP joint flexion were recorded for each of the 3 conditions.Results: The mean angle of PIP joint flexion prior to K-wire insertion was 87°, and the mean load applied was 241 g. The angles of flexion were 53° when the K-wire was placed through the extensor tendon, 70° when the K-wire was placed adjacent to the tendon, and 75° when the K-wire was placed into the base of P1 by going through the sagittal band, midway between the volar plate and the extensor tendon.Conclusions: K-wires placed remote from the extensor tendon create less of an immediate tether to PIP joint flexion than those placed through or adjacent to the extensor tendon.